SOUTH SUDAN THE IMPACT OF CONTEMPORARY ISSUES IN SOUTH SUDAN DEVELOPMENT - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Among all the good in the world, and all the progress being made in global issues, there is still much more to be done. Given the overwhelming disasters that nations, including the U.S., have been or still are going through, it is important to be aware of the most pressing global issues.